Flash X Ray: A Diagnostic Tool for Shaped Charge Studies - Tatake, S. G.; Kharat, D. K. (Defence Science Journal, 2013)
At present many antitank weapon systems are employing shaped charge warheads. It is, therefore, extremely important for a designer to avail of the methods capable of predicting performance of shaped charges, mainly to achieve maximum penetration. For this purpose, it is necessary to study the behaviour of the shaped charge during actual firing tests. These tests are difficult because of high speed of events that take place, production of intense light, smoke, debris, etc, and the large scale destruction caused. To overcome these difficulties, flash x-ray system during the jet studies on 30, 60 and 90 mm shaped charges and the evaluation of jet characteristics parameters.